1999
DOI: 10.1089/cap.1999.9.169
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Inattention-Overactivity, Aggression, and Stimulant Medication History as Predictors of Young Adult Outcomes

Abstract: This study examined the contributions of childhood symptom dimensions and aspects of methylphenidate (MPH) treatment to the prediction of young adult outcomes in boys who were referred to a child psychiatry outpatient clinic. They were diagnosed with hyperkinetic reaction of childhood/minimal brain dysfunction, and given MPH for an average of 30 months. Including significant effects and statistical trends, childhood Inattention-Over-activity was uniquely associated with fewer than 10% of adult outcomes such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
4
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 1 publication
1
57
4
2
Order By: Relevance
“…There were 5 prospective longitudinal studies: 2 involving children who were followed at least 4 years 14,21,22 and 3 involving children who were followed into young adulthood (Barkley RA et al, unpublished observations). 15,[23][24][25] One retrospective report was available from a study of adults with ADHD. 26 Overall, these studies comprised 674 medicated subjects and 360 unmedicated subjects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 5 prospective longitudinal studies: 2 involving children who were followed at least 4 years 14,21,22 and 3 involving children who were followed into young adulthood (Barkley RA et al, unpublished observations). 15,[23][24][25] One retrospective report was available from a study of adults with ADHD. 26 Overall, these studies comprised 674 medicated subjects and 360 unmedicated subjects.…”
Section: Resultsmentioning
confidence: 99%
“…One study in adults by Lambert et al 15 found a linear increase in smoking related to stimulant exposure in individuals with ADHD. In contrast, 1 study in adolescents 21 and 1 study in adults 24,25 reported that the risk for stable tobacco use was higher in individuals with ADHD who were not receiving stimulant treatment. No effect of stimulant treatment of ADHD on later risk for cigarette smoking was reported in 1 study of adolescents 14,22 and 1 in adults (Barkley RA et al, unpublished observations).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, the most important predictor of future development of a psychiatric disorder and of the degree of global impairment later in life is physical fighting in early childhood (Halperin et aI., 1995;Loeber et aI., 1992Loeber et aI., , 1993Loeber et aI., , 2000Paternite, Loney, Salisbury, & Whaley, 1999). Additionally, childhood physical aggression has frequently been demonstrated to be a useful grouping criterion in previous impulsivity studies (Dougherty, Bjork, et aI., 2000;Seguin, Boulerice, Harden, Tremblay, & Pihl, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Satterfield et al [33] showed that children who received longer multimodal treatment had better outcomes than children who discontinued treatment earlier; however, poorer family functioning may have been a factor in the group that dropped out of treatment. Paternite et al [34] also found that longer medication treatment was associated with fewer schizotypic features, better Minnesota Multiple Psychological Inventory scores [35], higher IQ scores, and better wide-range achievement scores in reading and arithmetic. The findings of Satterfield et al [33] and Paternite et al [34] differ from those of Fischer et al [36] and Lambert et al [37], who found that ADHD children who had longer treatment had more negative outcome.…”
Section: Prospective Follow-up Studiesmentioning
confidence: 99%